THE US GLOBAL CITIES AS HUBS FOR FOREIGN TRANSNATIONAL CORPORATIONS - M. E. Pilka; N. A. Sluka (Vestnik MGIMO-Universiteta, 2018)
Despite the acknowledgment of the global city concept and the importance of transnationalization processes in their formation, the debate regarding global city identification methods continues. The article stresses the need to change our approach in evaluating global cities by primarily looking at them as locales for foreign multinational corporations. By analyzing the location decisions of foreign TNCs included in the Forbes 2000 rankings two things become apparent: the “nodality” of US global cities and their hierarchical pattern. Moreover, the article recognizes the key role that Alpha global cities play by leading the country’s international business relations, examined through foreign TNCs. Using our methodology and data on foreign TNCs we defined five uneven groups of cities are defined in the study: city-hegemon New York, leading cities, heavyweight cities, middleweight cities and cities-outsider. The article defines some key factors that determine city’s attractiveness for foreign multinationals: its geo-economical power, functional specialization, location, historical and cultural ties, position on different sectoral markets. The study of US global cities as hubs for foreign transnational corporations seems to be especially useful for Russian cities, especially Moscow and St. Petersburgh, which aim to increase the attractiveness for foreign investment.